Hydropedology and Preferential Flow in the Tasmanian Texture‐Contrast Soils. Issue 4 (18th October 2013) - Hardie, Marcus; Doyle, Richard; Cotching, William; Holz, Greg; Lisson, Shaun
Abstract : The two‐way interaction between soil morphology and the processes governing soil water movement were investigated for a range of texture‐contrast soil profiles. The texture‐contrast soils consisted of a seasonally water‐repellent sandy loam A1 horizon over a bleached silica‐cemented A2e horizon and a mottled vertic clay subsoil. Differences in soil morphology and structure among sites had little influence on the proportion of soil that participated in infiltration or the maximum depth of infiltration; however, differences in subsoil structure influenced the processes by which water infiltrated and was stored within the B2 horizons. The occurrence of preferential flow was largely controlled by the effects of antecedent soil moisture content on water repellence in the A1 horizon, silica bridging in the A2e horizon, and clay shrinkage in the B2 horizons. Under dry soil conditions, infiltration resulted from up to five different forms of preferential flow. When soils were near field capacity, most forms of preferential flow ceased; however, wetting front instability and lateral flow developed in the A1 horizon. Preferential flows are not thought to have contributed to the pedogenesis of the texture‐contrast soils. Development of the contrasting soil texture horizons, sand infills, and bleached A2e horizons developed before and independently of the observed preferential flow processes in which reworked aeolian sands buried previously developed clay columns.